The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5935/0103-507x.20220003-en
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of a cluster-randomized clinical trial on adult general intensive care units in Brazil: TELE-critical care verSus usual Care On ICU PErformance (TELESCOPE) trial

Abstract: Objective: The TELE-critical Care verSus usual Care On ICU PErformance (TELESCOPE) trial aims to assess whether a complex telemedicine intervention in intensive care units, which focuses on daily multidisciplinary rounds performed by remote intensivists, will reduce intensive care unit length of stay compared to usual care. Methods: The TELESCOPE trial is a national, multicenter, controlled, open label, cluster randomized trial. The study tests the effectiveness of dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A cluster-randomised trial of TCC with a lower risk of bias will be available soon. 27 The only randomised trial of TCC of which we are aware found effects on protocol adherence but not patient outcomes. 5 Importantly, because of the (nearly) patient level randomisation and contamination from shared clinicians, our analysis of TECTONICS does not capture benefits to outcomes due to overall improvements in protocol adherence, discussed below.…”
Section: Discussionmentioning
confidence: 97%
“…A cluster-randomised trial of TCC with a lower risk of bias will be available soon. 27 The only randomised trial of TCC of which we are aware found effects on protocol adherence but not patient outcomes. 5 Importantly, because of the (nearly) patient level randomisation and contamination from shared clinicians, our analysis of TECTONICS does not capture benefits to outcomes due to overall improvements in protocol adherence, discussed below.…”
Section: Discussionmentioning
confidence: 97%
“…
The use of ventilator-free days (VFDs) as an outcome measure is increasingly popular in critical care research. (1)(2)(3) This composite outcome simultaneously reflects patient survival and the time not spent on mechanical ventilation (MV) within a specified timeframe, which usually extends from randomization up to Day 28. For patients who do not survive this period, VFDs are recorded as zero.Composite outcomes, such as those combining death, myocardial infarction, or stroke, are commonly used in fields such as cardiology due to their ability to enhance the statistical power of clinical trials while focusing on patient-relevant events.
…”
mentioning
confidence: 99%
“…The use of ventilator-free days (VFDs) as an outcome measure is increasingly popular in critical care research. (1)(2)(3) This composite outcome simultaneously reflects patient survival and the time not spent on mechanical ventilation (MV) within a specified timeframe, which usually extends from randomization up to Day 28. For patients who do not survive this period, VFDs are recorded as zero.…”
mentioning
confidence: 99%